Cancer Misinformation and Harmful Information on Facebook and Other Social Media: A Brief Report. (22nd July 2021) - Johnson, Skyler B; Parsons, Matthew; Dorff, Tanya; Moran, Meena S; Ward, John H; Cohen, Stacey A; Akerley, Wallace; Bauman, Jessica; Hubbard, Joleen; Spratt, Daniel E; Bylund, Carma L; Swire-Thompson, Briony; et al.
Abstract: There are few data on the quality of cancer treatment information available on social media. Here, we quantify the accuracy of cancer treatment information on social media and its potential for harm. Two cancer experts reviewed 50 of the most popular social media articles on each of the 4 most common cancers. The proportion of misinformation and potential for harm were reported for all 200 articles and their association with the number of social media engagements using a 2-sample Wilcoxon rank-sum test. All statistical tests were 2-sided. Of 200 total articles, 32.5% (n = 65) contained misinformation and 30.5% (n = 61) contained harmful information. Among articles containing misinformation, 76.9% (50 of 65) contained harmful information. The median number of engagements for articles with misinformation was greater than factual articles (median [interquartile range] = 2300 [1200-4700] vs 1600 [819-4700], P = .05). The median number of engagements for articles with harmful information was statistically significantly greater than safe articles (median [interquartile range] = 2300 [1400-4700] vs 1500 [810-4700], P = .007).